TET2 Mutations in Ph-Negative Myeloproliferative Neoplasms: Identification of Three Novel Mutations and Relationship with Clinical and Laboratory Findings. (25th May 2013) - Patriarca, Andrea; Colaizzo, Donatella; Tiscia, Gianluca; Spadano, Raffaele; Di Zacomo, Silvia; Spadano, Antonio; Villanova, Ida; Margaglione, Maurizio; Grandone, Elvira; Dragani, Alfredo
Abstract : High-throughput DNA sequence analysis was used to screen for TET2 mutations in peripheral blood derived DNA from 97 patients with BCR-ABL-negative myeloproliferative neoplasms (MPNs). Overall six mutations in the coding region of the gene were identified in 7 patients with an overall mutational frequency of 7.2%. In polycythemia vera patients (n = 25 ) 2 mutations were identified (8%), and in those with essential thrombocythemia (n = 55 ) 2 mutations (3.6%); in those with unclassifiable MPN (n = 8 ) 3 mutations (37.5%). No primary myelofibrosis patients (n = 6 ) harboured TET2 mutations. Three unreported mutations were identified (p.P177fs, p.C1298del, and p.P411del), the first two in patients with unclassifiable MPN, the last in a patient with essential thrombocythemia. On multivariate analysis the diagnosis of an unclassifiable MPN was significantly related to the presence of TET2 mutations (P = 0.02 ; OR: 2.81; 95% CI 1.11–7.06). We conclude that TET2 mutations occur in both JAK2 V617F-positive and -negative MPNs and are more frequent in MPN-U patients. This could represent the biological link between the different classes of myeloid malignancies.